Estudo do processo de infiltração em superfícies permeáveis a partir de um simulador de chuva por aspersão - Castro, Marcelo Henrique de (Universidade Federal do Tocantins, 2019)
This work had as a proposal to construct a rainfall simulator for studies of the infiltration process on permeable surfaces. First, it was necessary to build the rainfall simulator and make its calibration taking into account uniformity of application, real intensity, average drop diameter and kinetic energy generated by the simulator for the sprinkler and the work pressure chosen. Subsequently, the simulator built was used to simulate rainfall on three permeable surfaces: porous concrete blocks, concrete solid blocks and exposed soil. In the construction of the rainfall simulator stands out some points: among the sprinklers analyzed the 1/2 HH-36SQ was the one that presented the best Christiansen’s Uniformity Coefficient, the mean diameter of the rain drop produced by the sprinkler for pressure of 0.5 kgf/cm² was 2.23 mm, where the simulator had the ability to produce rainfall with kinetic energy equivalent to 90% of natural rainfall. Three precipitations with intensity of 79.11 mm/h were simulated on each surface type. The infiltration data observed on all surfaces were adjusted to the Horton model. Double ring infiltrometer was used in the soil to compare the steady-state infiltration rate obtained with the use of the rainfall simulator. The values found for the steady-state infiltration rates with the use of the rings were higher than the values seen with rainfall simulator. The surface that presented the largest steady-state infiltration rates (78.76, 78.69 e 78.57 mm/h) and the lowest coefficients of runoff (0.8840, 0.9121 e 0.7658) was with porous concrete blocks. Already the surface with concrete solid blocks was the one that had the lowest values of steady-state infiltration rate (5.97, 1.31 e 1.19 mm/h) and the highest coefficients of runoff (0.9812, 0.9927 e 0.9895).